In-Silico Design and Optimization of p-BaSi₂/n-Bi₂S₃ Heterojunction for Enhanced Photovoltaic Performance - Saksham Mathur (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This study aims to explore the integration of Bi2S3 as an electron transport layer (ETL) in BaSi2-based thin-film solar cells for the enhanced performance. Using the globally accepted SCAPS-1D simulation tool, a novel device architecture consisting of Al/SnO2:F/Bi2S3/BaSi2/Ni was systematically designed and optimized. Key optimization parameters include the thicknesses, carrier concentrations, bulk defect densities of each layer, interface defects, operating temperature, and the influence of series and shunt resistance on overall efficiency. The simulation results reveal that a BaSi2 layer with an optimized thickness of 1 µm and a doping concentration of 5 x 1019 cm-3, yields noteworthy outcomes. Specifically, champion efficiency (
Keywords: BaSi2; Bi2S3 ETL; Thin film solar cell; SCAPS-1D; Optimization; Simulation